How 3M manages its global laboratory network - Nicholson, Geoffrey C.
Geoffrey C. Nicholson outlines the strategies underlying 40 years of technical operations outside the United States
Labs outside the United States employ one-third of 3M's technical staff, emphasize technical service and spotting of new product opportunities.
As we approach the 21st century, global competitiveness requires a transnational organization. This is an organization with global vision and planning, yet with local responsiveness because of local customer requirements often driven by country specifications, standards and cultures. 3M's technical organization must reflect that vision to support the business opportunity, add technical content and hence compete in the global business arena. 3M's culture of innovation and creativity in developing new products is being exported to our technical operations outside the United States to maximize our market penetration using 3M's technological strengths.
Keywords: Global laboratory network